III STATUT LITEWSKI PO UPADKU RZECZPOSPOLITEJ W ROSYJSKIEJ LITERATURZE NAUKOWEJ XIX I POCZĄTKU XX WIEKU - Godek, Sławomir (Zeszyty Prawnicze, 2017)
The 3rd Statute of Lithuania in the Post-Partition Period in the Russian Science Literature in XIX and at the Beginning of the XX Century Summary In the Russian academic literature of the 19th and post-Partition history of the 3rdStatute of Lithuania was looked at in a numer of contexts. Above all, the Statute aroused interest as the primary source of bye-laws (local law) in the Western and Little Russian guberniyas of the Russian Empire. Its crucial importance for the codification undertaken of the law of these guberniyas was noted, and this on a backdrop of widespread and intense activity to reorganise Russian law. Most importantly, it was raised that the Statute formed the base material for the so-called Western Code of laws [Zwód zachodni] drawn up in the 1830s. The Lithuanian codification also aroused interest as one of the sources of the 10th volume of the Code of Laws [Swod Zakonow]. The Statute’s regulations were also brought up in the legal literature in order to show a deeper presentation of the nature of the then (i.e. nineteenth-century) institution of Russian law. In addition, the issue of the circumstances surrounding the gradual repeal of the Statute in specific areas of the Empire in 1831, 1840, 1842 was also tackled.